A study to detect important factors influencing purchasing product: A case study of home appliances - Amir Ghafurian Shagerdi; Koorosh Kohyari Haghighat; Amin Kohyari Haghighat; Amin Otoofi (Management Science Letters, 2013)
Home appliances are among basic requirements of anyone in the world and it is always important to find out about factors influencing this industry. Therefore, the purpose of this study is to provide a comprehensive model to detect major factors influencing on consumer purchasing intention. For this purpose, the proposed study designs a questionnaire and distributes it among 400 customers who have some experiences on purchasing home appliances in city of Tehran, Iran, recently. Cronbach alpha was calculated for all components of the survey and they were all well above the minimum acceptable level. We analyzed the data using structural equation modeling via LISREL and the results of this survey show that brand familiarity, brand trust, and perceived value have significant positive effects on consumers purchase intention.